HADITS TENTANG ETIKA GURU TERHADAP MURID - Marlina (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
A teacher must possess good character and ethics towards his or her students so that the knowledge transferred from the teacher to them will be more quickly absorbed and understood during the learning process. Ethics in a teacher is crucial, as it can influence the psychology and mental state of the students they teach. Therefore, a teacher must maintain good ethics to be able to communicate effectively and provide comprehensive understanding. To achieve optimal results, a teacher must possess good ethics towards his or her students. A teacher's responsibility arises from the dependent nature of the child, who will need assistance or guidance from the teacher. Therefore, ethics towards students is essential to maintain a balance between the teacher and the students. The advancement and development of education are in line with science and technology, so that changes in children's morals are greatly influenced by formal, informal, and non-formal education. Therefore, teachers are required to cultivate and maintain the morals of their students, ensuring they possess noble character by setting good ethical examples, as did the Prophet Muhammad (peace be upon him).